EVOLUTION OF THE PHOTOMETRIC PROPERTIES OF THE MAGNETIC CATACLYSMIC BINARY QQ VUL IN 1986-88 - Halevin, A. V.; Andronov, I. L.; Kolesnikov, S. V.; Kirneridze, G. N. (Одеські астрономічні публікації, 2017)
The long term activity variations of polar QQ Vul in 1986-88 are reported. Changes of the amplitude and the shape of phase eclipse curve are present. Moments of 20 minima are presented which are in a good agreement with the ephemeris by Andronov and Fuhrmann (1987, IBVS N 2976).